New Microfoundations for the Aggregate Matching Function. - Stevens, M (Blackwell Publishing Inc., 2007)
Empirical studies of the aggregate labor market matching function have favored a Cobb-Douglas functional form, for which there are no microfoundations in the existing literature. I present a new model for the matching process, based on a "telephone-line" Poisson queuing process, which, unlike other microeconomic approaches, can be integrated directly into standard theoretical search models. This implies a CES matching function, approximately Cobb-Douglas when search costs are approximately linear. The model allows empirical estimates of matching function parameters to be interpreted in terms of the costs and benefits of search.